ChemInform Abstract: Enhancement of Neighbouring‐Group Participation in Cu0‐Promoted Cross‐Coupling gem‐Difluoromethylenation of Aryl/Alkenyl Halides with 1, 3‐Azolic Difluoromethyl Bromides. Issue 4 (January 2015) - Jiang, Haizhen; et al., et al.
Abstract Two sets of slightly different reaction conditions are developed for the cross‐coupling of chelating and non‐chelating aryl halides with 2‐bromodifluoromethyl‐1, 3‐oxazoline to give the corresponding bis‐arylated difluoromethane derivatives.